Effect of Ultrasonic Power on the Microstructure and Properties of a Semi-Solid Slurry of SnSbCu11-6 Alloy - Lei Wang; Xiaobin Luo; Yuanwei Jia; Yongkun Li; Rongfeng Zhou; Hao Zhang; Dingdong Huo; Yao Li (Crystals)
In this paper, the ultrasonic vibration treatment (UVT) technique was used to prepare a SnSbCu11-6 alloy semi-solid slurry, and the effects of ultrasonic power on its microstructure size, distribution and properties were studied. The results show that the UVT technique significantly refines the Cu6Sn5 phase and SnSb phase and improves their distribution uniformity. Interestingly, the second SnSb phase is also well refined to nearly 100 °C below the melting point; furthermore, the morphology is transformed from coarse petal-like to fine regular cubic, and the average grain size is refined to 48.8 ± 8.8 μm. The alloy’s comprehensive properties are best when the ultrasonic power is 1200 W. The yield strength, tensile strength, elongation and microhardness reach 60.6 MPa, 70.3 MPa, 4.9% and 27.4 HV, respectively, which represent increases of 4.7%, 6.0%, 113% and 23.4%, respectively, compared with conventional liquid casting. This may be attributed to the grain size refinement and distribution uniformity enhancement of the Cu6Sn5 phase and the SnSb phase. This work provides a feasible and effective method for the preparation of high-performance tin-based babbitt alloys by UVT technology.